The Effect of Live Streaming Interactivity, Influencer Credibility, and Gamification Features on Consumer Impulse Buying in Tiktok Shop - Beby Eliza Sharon; Louis Tanady; Jeni Veronika Br Ginting; Agung Sahbana; Lina Kurniati (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The proliferation of social commerce has fundamentally reshaped consumer behavior, notably by amplifying the propensity for impulse buying on interaction-driven and entertainment-centric platforms such as TikTok Shop. This study examines the influence of Live Streaming Interactivity, Influencer Credibility, and Gamification features on consumer Impulse Buying within the TikTok Shop ecosystem in Indonesia. This study employs a quantitative, causal research design. Data were gathered via online surveys from 300 TikTok Shop users, selected through purposive sampling based on their prior engagement with live streaming and purchase history. Data analysis was executed using multiple linear regression via SPSS. The empirical findings reveal that Live Streaming Interactivity, Influencer Credibility, and Gamification each have a positive, statistically significant partial effect on Impulse Buying. Notably, Influencer Credibility emerged as the most dominant predictor. Furthermore, the simultaneous analysis confirms that these three variables significantly drive impulse buying behavior, yielding an Adjusted R^2 value of 0.313. This indicates that the proposed model accounts for 31.3% of the variance in consumer impulsive purchasing. These results validate the Stimulus–Organism–Response (S-O-R) framework within the social commerce context, where social, trust-based, and emotional stimuli collectively elicit impulsive behavioral responses. This research offers strategic insights for e-commerce practitioners on optimizing integrated marketing strategies through enhanced live-streaming engagement, influencer synergy, and gamified experiences